An urban school for District Six - Robertson, Alexander Graham (School of Architecture, Planning and Geomatics, 2017)
Why an urban school for District Six? The inspiration for this thesis was stimulated by various factors, the roots of which stem from the first term of 1965, when I was involved in a Redevelopment Scheme for District Six. As a student of Architecture, this exercise had a profound affect on me. It introduced to me vital considerations concerning Architecture of which, up until that time, I had only been superficially aware. It was necessary to study the anatomy of the city, to understand its complexity, before attempting to perform such a sensitive operation as a Redevelopment Scheme. To be one of a thousand designers in "a city of a thousand designers", it is just as necessary to be equipped with this understanding when involved with the design of an individual structure. This valuable exercise produced results of sufficient substance and merit to warrant it being carried a step further. The object of this thesis is to develop a school which will take its place in the proposed Redevelopment Scheme. The role of a school is an urban area such as District Six can be vitally important in cultivating a community within a slum and at the same time transforming it into a new world. A virtue must be made of increasing populations. Outdated suburban standards must be discarded - they have no place in a city. A new set of standards must be created to satisfy the needs of a rapidly expanding Twentieth Century urban environment. This is the challenge I have set myself.